Analysis of Public Service Quality in The Field of Population Administration at The Ratu Agung Subdistrict Office in Bengkulu City - Ridianto (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the quality of public services in the field of population administration at the Ratu Agung Sub-district Office in Bengkulu City. Population administration services are a form of basic service greatly needed by the public. This study employed a qualitative approach, with data collection techniques through in-depth interviews, observation, and documentation. The analytical framework used in this study is the SERVQUAL theory by Parasuraman et al., which encompasses five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results indicate that the quality of public services at the Ratu Agung Sub-district Office is generally considered good, although several challenges remain, such as limited service space and human resources, as well as network disruptions that impact service speed. The implications of this study highlight the importance of improving infrastructure, strengthening staff competencies, and developing a more effective digital population service system. It is hoped that the results of this study can serve as evaluation material and input for the sub-district government in order to improve the quality of public services that are prime and oriented towards public satisfaction.